HUBUNGAN PENERAPAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KEPUASAN PASIEN - Transyah, Chichi Hafifa; Toni, Jerman (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Therapeutic communication includes interpersonal communication with the starting point of mutual understanding between nurses and patients. The average data obtained from several hospitals in Indonesia shows 67% of patients who complain of dissatisfaction in the acceptance of health services, Based on the initial survey that researchers have done on October 20, 2016 at RSUD dr. Rasidin padang by interview 10 patients 4 people said friendly nurse, 6 people said normal because nurses do not explain to the patient what the purpose of the actions performed, nurses do not smile, do not introduce themselves and nurses do not Reminded to seek treatment again.The research design used is descriptive analytic. The study was conducted in October 2016 until August 2017 in the internal ward of RSUD dr. Rasidin Padang in 228 populations with 76 samples. Samples are taken by accidental sampling. The data were processed univariate using frequency distribution and bivariate by using chi square.Â The results showed that more than half of 64% of patients were dissatisfied with the implementation of therapeutic communication nurses. More than half of 74% of nurses lacked therapeutic communication to patients. So there is a significant relationship between patient satisfaction with the implementation of therapeutic communication nurse in inpatient ward of RSUD dr. Rasidi Padang in 2017 (p = 0.003).The conclusion of the study that there was a significant relationship between the implementation of therapeutic communication with patient satisfaction in the internal ward of RSUD dr. Rasidi Padang in 2017.Â Komunikasi terapeutik termasuk komunikasi interpersonal dengan titik tolak saling memberikan pengertian antar perawat dengan pasien. Rata-rata hasil data yang didapatkan dari beberapa rumah sakit di Indonesia menunjukan 67% pasien mengeluh adanya ketidakpuasan dalam penerimaan pelayanan kesehatan, terutama dalam hal komunikasi. Tujuan penelitian ini adalah untuk mengetahui hubungan penerapan komunikasi terapeutik dengan kepuasan pasien di ruang rawat inap interne RSUD dr. Rasidin Padang 2017.Desain penelitian yang digunakan adalah deskriptif analitik. Penelitian telah dilakukan pada bulan Oktober 2016 sampai dengan Agustus 2017 di ruang rawat inap interne RSUD dr. Rasidin Padang dengan 228 populasi dan 70 orang sampel. Sampel diambil secara accidental sampling. Data diolah secara univariat menggunakan distribusi frekuensi dan secara bivariat dengan menggunakan chi square. Hasil penelitian menunjukkan bahwa lebih dari separoh yaitu 64% pasien tidak puas dengan pelaksanaan komunikasi terapeutik perawat. Lebih dari separoh yaitu 74% perawat kurang melakukan komunikasi terapeutik terhadap pasien. Jadi terdapat hubungan yang bermakna antara kepuasan pasien dengan pelaksanan komunikasi terapeutik perawat di ruang rawat inap interne RSUD dr. Rasidi Padang tahun 2017 (p= 0,003 (< 0,05). Simpulan penelitian bahwa terdapat hubungan yang bermakna antara penerapan komunikasi terapeutik dengan kepuasan pasien di ruang rawat inap interne RSUD dr. Rasidi Padang tahun 2017.Â